DNA Polymerases in Biotechnology (2015)
DNA polymerases are core tools for molecular biology including PCR, whole genome amplification, DNA sequencing and genotyping. Research has focused on discovery of novel DNA polymerases, characterization of DNA polymerase biochemistry and development of new replication assays. These studies have accelerated DNA polymerase engineering for biotechnology. For example, DNA polymerases have been engineered for increased speed and fidelity in PCR while lowering amplification sequence bias. Inhibitor resistant DNA polymerase variants enable PCR directly from tissue (i.e. blood). Design of DNA polymerases that efficiently incorporate modified nucleotide have been critical for development of next generation DNA sequencing, synthetic biology and other labeling and detection technologies. The Frontiers in Microbiology Research Topic on DNA polymerases in Biotechnology aims to capture current research on DNA polymerases and their use in emerging technologies.